1994
DOI: 10.1093/rheumatology/33.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Activity of Serum Creatine Kinase in Rheumatoid Arthritis: A Phenomenon Linked to the Inflammatory Response

Abstract: In a case-controlled study, serum creatinine kinase (CK) activity was significantly lower in 40 patients with RA than in 40 age- and sex-matched patients with non-inflammatory arthropathies [mean 37.6 (S.D. 29.2) vs 77.7 (S.D. 45.3) IU/l respectively P < 0.0001]. In contrast, serum levels of aldolase and myosin were not significantly lower in RA patients. A significant inverse correlation between CK activity and ESR, CRP and platelet count was observed in RA. There was also a positive correlation between haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…[12]. This might also be the case of our patient with an active symmetrical but non-erosive arthritis, although to our knowledge this finding has not yet been reported in polymyositis.…”
supporting
confidence: 64%
“…[12]. This might also be the case of our patient with an active symmetrical but non-erosive arthritis, although to our knowledge this finding has not yet been reported in polymyositis.…”
supporting
confidence: 64%
“…These facts make it questionable that GPI plays the same important role in human RA than it does in the K/BxN mouse model. The facts that RA patients have lower serum levels of CK-M and muscle weakness is sometimes reported make it appear worthwhile to examine the relevance of CK-M for the pathogenesis and diagnostic of RA [84]. Another aspect of antigen specificity being widely discussed is the finding of high reaction specificity against citrullinated peptides in the serum of RA patients.…”
Section: Ubiquitous Autoantigensmentioning
confidence: 99%
“…Several studies have shown that CK activity is reduced in a number of conditions, including inflammatory rheumatic diseases [3][4][5][6]. Recently, Sanmarti et al [4] showed an inverse correlation between CK activity and inflammatory activity in inflammatory rheumatic diseases.…”
Section: Introductionmentioning
confidence: 99%